5x² + 3x - 8 > 0
5x² + 3x - 8 = 0
D = 9 + 8·4·5 = 169 = 13²
5(x - 1)(x + 1,6) > 0
(x - 1)(x + 1,6) > 0
x ∈ (-∞; -1,6) U (1; +∞)
(2x² - 3x + 1)(x - 3) ≥ 0
2x² - 3x + 1 = 0
D = 9 - 2·4 = 1
2(x - 1)(x - 0,5)(x - 3) ≥ 0
(x - 1)(x - 0,5)(x - 3) ≥ 0
- 0,5 + 1 - 3 +
• • • > x
x ∈ [0,5; 1] U [3; +∞)
x² - 2x - 15 ≥ 0
x² - 2x + 1 - 4² ≥ 0
(x - 1)² - 4² ≥ 0
(x - 1 - 4)(x - 1 + 4) ≥ 0
(x - 5)(x + 3) ≥ 0
x ∈ (-∞; -3] U [5; +∞)
Нули числителя: x = -1; 2/3; 2,5.
Нули знаменателя: x = -3; 1
- -3 + -1 - 2/3 + 1 - 2,5 +
°• • °• > x
ответ: x ∈ (-3; -1] U [2/3; 1) U [2,5; +∞).
Подробнее - на -
Пошаговое объяснение:
717b - 84b + 88c = 633b + 88c
b = 2 и c = 5
633 * 2 + 88 * 5 = 1266 + 440 = 1706
(d + c) * 25 + 34d = 25d + 25c + 34d = 59d + 25c
d = 7 и c = 5
59 * 7 + 25 * 5 = 413 + 125 = 538
546b + (a - b) * 26 = 546b + 26a - 26b = 520b + 26a
b = 2 и a = 6
520 * 2 + 26 * 6 = 1040 + 156 = 1196
(d + c) * 34 - 42d = 34d + 34c - 42d = 34c - 8d
c = 5 и d = 7
34 * 5 - 8 * 7 = 170 - 56 = 114